Efektifitas Pemberian Salep VCO Pada An. R Dengan Masalah Utama Gangguan Integritas Kulit di Desa Kalikajar - Fitriyani, Agil Puji; Sulistyowati, Priyatin; Ningtyas, Rahaju (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Background : Children are the main asset in preparing the next generation of family, society and country. In the process of child growth and development is much influenced by various factors both genetic, environmental, biological. Skin disease is a skin disorder caused by fungi, germs, parasites, viruses or infections that can affect anyone of any age. Treatment for children can be done by administering VCO ointment, lindane lotion, crotamiton cream and maintaining personal hygiene. Purpose: this study aims to determine the effectiveness of VCO ointment on children who suffer from impaired skin integrity. Methods: This study uses a qualitative descriptive method with a nursing care approach by conducting nursing care as the unit of analysis. Methods of data collection by interviews, observation, physical examination. Results: The results of the implementation of nursing, the meeting before the action the wound looked dry scaly, skin color around the ping, wound length 15cm and width 7 cm and after nursing for 15 days the wound looked moist, skin color around the ping, wound length 15cm and width 6 cm, states that VCO ointment has an effect on wound healing, impaired skin integrity. Conclusion: the effectiveness of giving VCO ointment to children who suffer from impaired skin integrity is resolved